تصميم وتطوير نظام إدارة التعلم - هاجر, غرايسة; مريم, بوقنعة (university of eloued جامعة الوادي, 2022)
في هذا المذكرة، نحن مهتمون بتصميم وتطوير نظام إدارة التعلم ) LMS (. كمنصة تفاعلية الهدف الرئيسي هو تعزيز عملية التعلم في ظل جائحة ك ورونا من خلال توفير قناة تفاعل بين المعلمين والمتعلمين وتبسيط بعض المهام التعليمية مثل الإش ا رف والتقييم من خلال وظائف متعددة مثل إرسال التقارير والعمل الشخصي والتبادل المستندات والملاحظات والتعليقات.In this report, we are interested to design and development of a Learning Management System (LMS). As interactive platform, the main objective is to enhance the learning process in light of the Corona pandemic by providing interaction channel between tutors and learners and simplifying some educational tasks such as supervision and evaluation through the multiple functions such as sending reports, personal work, exchanging documents , notes and comments.
مذكرة ليسانس اعلام الي
Keywords: التعلم , كوفيد - 91 نظام ادارة التعليم، منصة تفاعلية.; learning, LMS, COVID-19, interactive platform